Comparison of Effects of Anti-thrombin Aptamers HD1 and HD22 on Aggregation of Human Platelets, Thrombin Generation, Fibrin Formation, and Thrombus Formation Under Flow Conditions - Derszniak, Katarzyna; Przyborowski, Kamil; Matyjaszczyk, Karolina; Moorlag, Martijn; de Laat, Bas; Nowakowska, Maria; Chlopicki, Stefan (Frontiers in Pharmacology, 2019)
HD1 and HD22 are two of the most-studied thrombin exosite I- and exosite II- binding aptamers. To complete of their pharmacological profiles, the effects of HD1 and HD22 on thrombin-, ristocetin- and collagen-induced human platelet aggregation, on thrombin generation and fibrin formation in human plasma, as well as on thrombus formation in human whole blood using Total Thrombus-formation Analysis System, were assessed. The dissociation constants for HD1 and HD22 complexes with thrombin in simulated plasma ionic buffer were also evaluated. HD1 was more potent than HD22 in terms of inhibiting thrombin-induced platelet aggregation in platelet-rich plasma (PRP; 0.05 – 3 µM) and in washed platelets (WP; 0.005 – 3 µM): approximately 8.31% (± 6.99% S.D.) and 89.53% (± 11.38% S.D.) for HD1 (0.5 µM) and HD22 (0.5 µM), respectively. Neither HD1 nor HD22 (3 µM) did influence platelets aggregation induced by collagen. Both of them inhibited ristocetin-induced aggregation in PRP. Surprisingly, HD1 and HD22 aptamers (3 µM) potentiate ristocetin-induced platelet aggregation in WP. HD1 reduced thrombin generation in a concentration-dependent manner (at 3 µM ETP 1677.53 ± 55.77 [nM‧min] vs control 2271.71 ± 423.66 [nM‧min]), inhibited fibrin formation (at 3 µM 33.70 min ± 8.01 min vs control 7.91 min ± 0.91 min) and reduced thrombus formation under flow conditions in T-TAS system (at 3 µM AUC30 758.30 ± 344.23 [kPa‧min] vs control 1553.84 ± 118.03 [kPa‧min]). HD22 (3 µM) also prolonged thrombin generation but increased the thrombin peak. HD22 (3 µM) shortened the lag time of fibrin generation (5.40 min ± 0.26 min vs control 7.58 min ± 1.14 min) but did not modify thrombus formation (3, 15 µM). Kd values for the HD1 complex with thrombin was higher (257.8 ± 15.0 nM) than the Kd for HD22 (97.6 ± 2.2 nM). In conclusion, HD1 but not HD22 represented a potent anti-thrombotic agent, confirming the major role of exosite I in the action of thrombin. HD22 aptamer blocking exosite II displays weaker anti-platelet and anti-coagulant activity, with surprising activating effects on thrombin and fibrin generation most likely induced by HD22-induced allosteric changes in thrombin dynamic structure.